2013
DOI: 10.1002/jobm.201200483
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning and functional characterization of MnSOD from Dunaliella salina

Abstract: Dunaliella salina, a unicellular green alga, has the potential to grow in hypersaline environments via one of its gene products, superoxide dismutase (SOD). The superoxide radicals (O2 (-) ) produced by environmental stresses can cause damage to cells, and SOD catalyzes the turnover of such free radicals to protect cells. In this study, the gene coding for SOD in D. salina was cloned and the product was further identified and characterized. The open reading frame of this gene was 651 bp long, encoding for 217 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 41 publications
(51 reference statements)
0
5
0
Order By: Relevance
“…Of these, CuZnSOD has different primary and tertiary structures compared to Fe/MnSOD and has almost certainly evolved independently . Previous studies have reported that both transcription and enzymatic activity of SODs are sensitive to environmental stresses such as exposure to heavy metals, biocides, and/or heat shock . For these reasons, SOD has been frequently used as an ecotoxicological biomarker in many aquatic organisms …”
Section: Introductionmentioning
confidence: 99%
“…Of these, CuZnSOD has different primary and tertiary structures compared to Fe/MnSOD and has almost certainly evolved independently . Previous studies have reported that both transcription and enzymatic activity of SODs are sensitive to environmental stresses such as exposure to heavy metals, biocides, and/or heat shock . For these reasons, SOD has been frequently used as an ecotoxicological biomarker in many aquatic organisms …”
Section: Introductionmentioning
confidence: 99%
“…S6). Similarly, it has been reported that E. coli expressing the MnSOD from Dunaliella salina displays resistance to concentrations higher than 10 % (1.7 M NaCl) [42]. Remarkable E. coli expressing the recombinant CtSOD from C. thermophilum displays high salt tolerance (up to 3 M NaCl), indicating that it is an excellent stress protectant protein [36].…”
Section: Effect Of H 2 O 2 and Saltmentioning
confidence: 67%
“…Dunaliella parva is a unicellular halophilic green alga, which simultaneously accumulates lipids and large amounts of carotenoids (primarily beta-carotene), and shows a good resistance against unfavorable ambient conditions such as UV-A radiation, salinity up-shock, extreme pH and temperature, and nitrogen limitation (Mogedas et al, 2009;Borowitzka, 2013;Zhang et al, 2014;Srinivasan et al, 2015). In addition, D. parva has no rigid cell wall, which is favorable for genetic manipulation and extraction (Hosseini-Tafreshi and Shariati, 2009;Barzegari et al, 2010).…”
Section: Introductionmentioning
confidence: 99%